Conventional weight loss therapy in morbid obesity during COVID-19 pandemic: degree of burdens at baseline and treatment efficacy - Schraml, Jessica; Bauer, Kerstin; Schild, Sandra; Klos, Bea; Erschens, Rebecca; Stengel, Andreas; Nieß, Andreas; Zipfel, Stephan; Mack, Isabelle (Frontiers in Psychiatry, 2024)
Introduction COVID-19 affected global physical and psychological health. The purpose of this study was to explore the pandemics impact on health-related quality of life (HRQoL), mental health (anxiety, depression, and perceived stress) and eating behavior in people with severe obesity participating in a multimodal conservative behavioral weight loss (BWL) program conducted via videoconferencing. Additionally, the efficacy of the six-month BWL program in a virtual video-based setting during the pandemic was examined. Methods 297 participants of a face-to-face multimodal behavioral weight loss program prior to the pandemic (PrePAN, May 2014–September 2019) and 146 participants of the in terms of content same intervention in a videoconference-based setting during the pandemic (PAN, July 2020–April 2022) were questioned and compared using standardized questionnaires for HRQoL, symptoms of depressive and anxiety disorders, perceived stress, and eating behavior at baseline and at the end of treatment. Results Symptoms for anxiety, depression and perceived stress were similar between PrePAN and PAN at baseline. In addition, PAN tended to show lower disinhibition of eating behavior and feelings of hunger than PrePAN. During the pandemic, the BWL intervention resulted in body weight loss (67%) or stabilization (16%) in most of the participants. It also contributed by improving physical HRQoL, lower worries, and improved eating behaviors compared to baseline. Conclusion During the COVID-19 pandemic, baseline mental health of people with morbid obesity was not worse than before the pandemic. Additionally, the BWL intervention in the virtual video-based setting stabilized and improved physical and mental health during the COVID-19 pandemic.